RETROPERITONEAL LIPOSARCOMA-EXCISION OF RETROPERITONEAL TUMOR AND RIGHT NEPHRECTOMY: A CASE STUDY - VENKATA YASESWI, NAMALA; KUMAR T, VINAY; VYDURYAM, KOMMURI; KOMMURI JOY SHALEM, ZAKIRA BEGUM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
A 64-year-old woman was referred to the hospital with complaints of abdomen right side tightness with discomfort for 1 month. Computed tomography scan of abdomen investigation revealed large retroperitoneal mass measuring 18.9 cm × 12.1 cm displacing the inferior vena cava right kidney and renal vessels in right hypochondriac and lumbar regions of the abdomen with large fat components. She underwent surgery, which involves the resection of tumor mass with non-affected surgical margins. These tumors tend to be resistant to radiotherapy or chemotherapy. Among the most important prognostic factor related to survival is surgery with non-affected margins. A review on etiology, pathophysiology, pathological classification, and grading is explained in literature review.